(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This publication examines the impact of George Gordon Byron’s literary heritage on the artistic world of Mikhail Lermontov. It emphasizes that the Russian classic creatively adapted key elements of Byronic aesthetics: the cult of the rebellious individual, the thirst for independence, and the pathos of civic duty. At the same time, Lermontov’s originality was inextricably linked to his national roots and was shaped by the realities of Russian society of that era.